Mussolini's Nature: An Environmental History of Italian Fascism - Armiero, Marco; Hardenberg, Wilko Graf von; Biasillo, Roberta; Sievert James (Cambridge, Massachusetts : The MIT Press, 2022)
"Explores how Mussolini's regime developed a political ecology that mobilized nature to legitimize and serve fascist interests"
Keywords: Fascism -- Italy; Political ecology -- History -- 20th century -- Italy; Environmental policy -- History -- 20th century. -- Italy